1993
DOI: 10.1038/clpt.1993.46
|View full text |Cite
|
Sign up to set email alerts
|

Protein binding and ivermectin estimations in patients with onchocerciasis

Abstract: We measured ivermectin in plasma, urine, and saliva of nine patients with onchocerciasis. The aim was to establish pharmacokinetic parameters and to assess the most facile medium for use in monitoring compliance. Binding of ivermectin to plasma proteins in vitro was also investigated. The mean (+/- SEM) plasma values for the nine subjects were as follows: weight, 66.3 +/- 2.8 kg; dose, 11.11 +/- 0.4 mg; half-life, 56.50 +/- 7.01 hours; clearance, 142.5 +/- 22.6 L/kg; volume of distribution, 9.91 +/- 2.67 L/kg;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 0 publications
1
25
0
3
Order By: Relevance
“…In onchocerciasis patients, with 6 mg (tablet), the volume of distribution of the area (V λ ) was 9.9 l·kg −1 and the mean residence time (MRT) was 3.7 days (16).…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In onchocerciasis patients, with 6 mg (tablet), the volume of distribution of the area (V λ ) was 9.9 l·kg −1 and the mean residence time (MRT) was 3.7 days (16).…”
Section: Distributionmentioning
confidence: 99%
“…Such avid binding assumes great importance as the drug is administered in world areas where malnutrition and hypoalbuminemia are common, so in these patients a decrease in plasma proteins and, consequently, a higher free fraction of ivermectin could be expected. Nevertheless, acetylsalicylic acid does not interfere with ivermectin binding (16).…”
Section: Distributionmentioning
confidence: 99%
“…Compliance to non-observed ivermectin therapy in mass drug administration programs could be assessed through plasma concentration monitoring [88]. …”
Section: Resultsmentioning
confidence: 99%
“…The increased permeability of the digestive epithelium to plasma proteins in the gastrointestinal lumen reduces the half-life of plasma albumin and immunoglobulin up to 50% (Barriga 1996). Binding studies in humans and dogs showed that ivermectin bound extensively to plasma proteins (Okonkwo et al 1993), including albumin and lipoproteins (Rohrer and Evans 1990). Consequently, plasma protein leakage into the gut might have been an important factor for increasing the fecal excretion of DRM and reducing the tissue distribution of the drug in the parasitized lambs in this study.…”
Section: Analytical Methodology Validationmentioning
confidence: 97%